Measuring experiential qualities of urban public spaces: users' perspective - Zamanifard, Hadi; Alizadeh, Tooran; Bosman, Caryl; Coiacetto, Eddo (Journal of urban design, 2019)
This paper presents an index for measuring experiential qualities (EQs) of urban public spaces through users' perspective. The index is underpinned by interrelated qualities of comfort, diversity and vitality, inclusiveness, and image and likeability. It is then applied to two public spaces in the Australian city of Brisbane: Queen Street Mall and South Bank Parklands. The index extends the user-centred measuring tools and can be used by practitioners, authorities and scholars to highlight users' needs and concerns. Findings from case spaces revealed deficiencies and provided a deeper insight into EQs through integrating urban design qualities, perception and management measuring items.